Feeling the class: Class identities, emotions and political attitudes in Perama Ship Repair Zone - Bithymitris, Giorgos (The Greek Review of Social Research, 2019)
With the current paper, we explore the components of class identities as manifested in the discourse of workers from the Ship Repair Perama Zone within a multilevel crisis context. Focusing on core elements of the class identity, we analytically distinguish the following factors that shape it: a) the occupational dispositions of the workers, b) their ties with the unions, c) their political attitudes, d) the emotions that accompany their identity, which is constituted through their narratives.